The Effect of Loyalty on Employee Performance at SAMSAT Corner Sun Plaza Medan - Cia Cai Cen (International Journal of Economics (IJEC), 2022)
Basically the employees of Samsat Corner Sun Plaza Medan already have loyalty to the leadership, existing systems and regulations, but it is undeniable that in reality not all employees have the same level of loyalty, because sometimes there are still employees who do things that reflect employee disloyalty. The formulation of the problem in this study is whether there is and how much influence loyalty has on the performance of Samsat Corner Sun Plaza Medan employees. This study used a questionnaire instrument in the form of a questionnaire given to 20 respondents. Technical analysis of the data used is based on product moment correlation coefficient, hypothesis testing and determination test. After processing the data and testing the data, from the calculation of the product moment correlation coefficient, a positive value is obtained, this means that the relationship between the two variables studied is positive with a correlation value of 0.65. There is a positive and significant influence between the influence of loyalty on performance at Samsat Corner Sun Plaza Medan as evidenced from the results of the calculation of the hypothesis test obtained t count = 4.68975 while the t table in n-2 (20-2) which is 2.101 at a significant level of 0.05 (α = 5%) it can be seen that the t count > t table that is 4.68975 > 2.101. So there is an influence between loyalty to performance at Samsat Corner Sun Plaza Medan and the hypothesis is accepted. The percentage of the influence of loyalty on performance at Samsat Corner Sun Plaza Medan is From the calculation of the determination test, it can be seen that the X variable affects the Y variable by 42.25 %, while 57.75 % is influenced by factors not examined in this study.